2021
DOI: 10.1016/j.rmcr.2021.101473
|View full text |Cite
|
Sign up to set email alerts
|

Culture-negative pleural empyema after Coronavirus disease-19 resolution – A case report

Abstract: Even after more than a year, novel Coronavirus disease-19 (COVID-19) clinical presentation and complications are still being reported. We present a 75-year-old patient with culture-negative pleural empyema a month after COVID-19 resolution without re-infection. We hypothesize that culture-negative empyema can be present in patients with immune defect, e.g., elderly or diabetic patients, and prior antibiotic exposure. Empyema after COVID-19 resolution may be related to delayed inflammation improvement in chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…While, to this date, there have been no other reports of patients with concurrent COVID-19 and Actinomyces meyeri infection within the literature, empyema in relation with COVID-19 positive patients have primarily been seen in hosts who are immunocompromised, have autoimmune diseases, or have had prior antibiotic exposure. 18 SARS-CoV studies have demonstrated that the virus infects epithelial cells in the lung which induces interleukin-8 (IL-8) production. 18 IL-8, a prominent interleukin in attracting T-cells and neutrophils, recruits a large number of inflammatory cells which are able to further induce damage to weaken the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While, to this date, there have been no other reports of patients with concurrent COVID-19 and Actinomyces meyeri infection within the literature, empyema in relation with COVID-19 positive patients have primarily been seen in hosts who are immunocompromised, have autoimmune diseases, or have had prior antibiotic exposure. 18 SARS-CoV studies have demonstrated that the virus infects epithelial cells in the lung which induces interleukin-8 (IL-8) production. 18 IL-8, a prominent interleukin in attracting T-cells and neutrophils, recruits a large number of inflammatory cells which are able to further induce damage to weaken the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…18 SARS-CoV studies have demonstrated that the virus infects epithelial cells in the lung which induces interleukin-8 (IL-8) production. 18 IL-8, a prominent interleukin in attracting T-cells and neutrophils, recruits a large number of inflammatory cells which are able to further induce damage to weaken the lung parenchyma. 19 We considered that in our patient with adequate oral hygiene and no history of alcoholism, the recent hospitalization and the concurrent COVID-19 infection were the most important risk factors for the A. meyeri empyema infection.…”
Section: Discussionmentioning
confidence: 99%
“…In the first stage of a pleural empyema, the optimal treatment may be appropriate antibiotic therapy and pleural drainage. 8 This approach in the treatment of a pleural empyema in the course of SARS‐CoV‐2 infection has proven effective in the patients described by Zavin et al and Silalahi et al 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In the first stage of a pleural empyema, the optimal treatment may be appropriate antibiotic therapy and pleural drainage. 8 This approach in the treatment of a pleural empyema in the course of SARS-CoV-2 infection has proven effective in the patients described by Zavin et al and Silalahi et al 17,18 Regarding the surgical approach, video-assisted thoracic surgery (VATS) is considered the "gold standard for the surgical management of an empyema." 19 VATS enables the proper decortication of an empyema as effectively as thoracotomy, and is associated with less pain and, at the same time, greater patient acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…BUMDes sebagai lembaga yang dibentuk untuk mensejahterakan masyarakat mengalami dampak yang cukup signifikan dimasa pandemi covid-19 (Stafford, Parchem, and Sibai 2021;Silalahi and Suwita 2021). Persoalan ekonomi yang dihadapi oleh BUMDes maupun masyarakat semakin kompleks akibat pendemi COVID-19.…”
Section: Hasil Dan Pembahasanunclassified